New advantageous tool in single incision laparoscopic cholecystectomy: the needle grasper - Turgut Donmez; Sinan Uzman; Sina Ferahman; Suleyman Demiryas; Engin Hatipoglu; Server Sezgin Uludag; Dogan Yildirim (Videosurgery and Other Miniinvasive Techniques)
Introduction: During single-incision laparoscopic cholecystectomy (SILC), the gallbladder is suspended with stitches, resulting in perforation risk and difficulty in exploration. Aim: We used the needle grasper in SILC to hang and manipulate the gallbladder. Material and methods : Sixty-five patients (43 female, 22 male) who underwent SILC between December 2013 and December 2014 were analyzed retrospectively for patient demographics, duration of operation, laparotomy or conventional laparoscopy necessity, drain use, complications, and hospital stay periods. To place the SILC port (Covidien, Inc.), the needle grasper was inserted at the right upper abdominal quadrant without an incision to hang and manipulate the gall-bladder. Results : The mean age was 47.9 ±13.068 years; the mean body mass index (BMI) was 26.94 ±3.913 kg/m2. ASA scores were 1, 2, and 3. Two patients with high BMI with additional trocar use were excluded. The operations were completed without any additional trocar in 59 patients. The mean operation time was 89 ±22.41 min. Eighteen patients required a drain; all were discharged after drain removal. One patient needed re-hospitalization and percutaneous drainage and was discharged on the 9th day. Fifty-three patients were discharged on the 1st post-operative day. Eleven patients with drains were discharged on the 2nd day, and 1 was discharged on the 7th day. The mean hospital stay period was 1.26 ±0.815 days. Conclusions : The main difficulty of SILC is to manipulate hand tools because the triangulation principle of laparoscopy use is not possible in SILC. Inserting a needle grasper into the abdominal cavity at the right subcostal area to manipulate the gallbladder helps and does not leave a visible scar.